An overview of assessment of prognostic and predictive factors in breast cancer needle core biopsy specimens. Issue 12 (14th July 2007) - Rakha, E A; Ellis, I O
Abstract : Needle core biopsy (NCB), as part of triple assessment for preoperative evaluation and diagnosis of breast cancer, is now considered as an established, highly accurate method for diagnosing breast cancer that has replaced either fine needle aspiration cytology or excisional biopsy as the initial diagnostic biopsy procedures in many institutions. In addition to its primary role in establishing an accurate histological diagnosis, NCB can potentially provide important additional pathological prognostic information which may be of direct clinical value in certain situations, such as patients being considered for preoperative (neoadjuvant) therapy. With this background in mind we briefly review the current role of NCB in breast cancer diagnosis and then concentrate this review on the usefulness and issues relating to use of this technique in providing accurate, reliable and clinically relevant preoperative prognostic and predictive information in patients with breast cancer.